2006
DOI: 10.1038/sj.embor.7400835
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of transcription in intermediate heterochromatin

Abstract: Constitutive heterochromatin is a compact, transcriptionally inert structure formed in gene-poor and repeat-and transposon-rich regions. In Arabidopsis, constitutive heterochromatin is characterized by hypermethylated DNA and histone H3 dimethylated at lysine (K) 9 (H3K9me2) together with depletion of histone H3 dimethylated at lysine 4 (H3K4me2). Here, we describe loci with intermediate properties of heterochromatin in which transcription downregulation is inherited in a manner similar to constitutive heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
117
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(128 citation statements)
references
References 23 publications
10
117
1
Order By: Relevance
“…Previous studies showed that DNA methylation in mom1 mutants was similar to the wild-type level (17)(18)(19)21). This observation was recently confirmed by genome-wide bisulfite-sequencing (BS-seq) analyses (43).…”
Section: Atmorc6 and Mom1 Act Synergistically To Silence A Common Set Ofsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies showed that DNA methylation in mom1 mutants was similar to the wild-type level (17)(18)(19)21). This observation was recently confirmed by genome-wide bisulfite-sequencing (BS-seq) analyses (43).…”
Section: Atmorc6 and Mom1 Act Synergistically To Silence A Common Set Ofsupporting
confidence: 57%
“…The mom1 mutant shows a loss of transcriptional gene silencing at loci located predominantly in the pericentromeric regions of the chromosomes (18). Interestingly, these transcriptional gene-silencing defects occur without major changes in DNA methylation or histone marks (17)(18)(19)(20)(21). RNA Polymerase IV and V (PolIV and PolV), which are key components of the RdDM pathway, were identified as enhancers of the mom1 phenotype (18).…”
mentioning
confidence: 99%
“…The involvement of MOM1 in transcriptional silencing is independent of changes in DNA methylation in heterochromatin regions and remains a poorly understood silencing mechanism in plants (Habu et al, 2006;Vaillant et al, 2006;Yokthongwattana et al, 2010). Previous reports showed that SUMO proteins and SUMO-conjugating enzymes mediate transcriptional repression at heterochromatin regions in yeast and animals (Shiio and Eisenman, 2003;Shin et al, 2005;Nathan et al, 2006), but it is unknown whether and how these proteins function at heterochromatin regions in plants.…”
Section: Discussionmentioning
confidence: 99%
“…RdDM components tend to target the euchromatic regions of chromosome arms (Huettel et al, 2006;Cokus et al, 2008;Zemach et al, 2013), whereas MOM1 preferentially targets pericentromeric heterochromatin regions (Habu et al, 2006;Yokthongwattana et al, 2010). We localized upregulated TEs identified in nrpe1, mom1, and pial1/2 on five Arabidopsis chromosomes.…”
Section: Pial1 and Pial2 Share Common Targets With Mom1mentioning
confidence: 99%
“…Central components of the RdDM machinery are the plant-specific RNA polymerases IV and V in which NUCLEAR RNA POLYMERASE D1 (NRPD1) and NUCLEAR RNA POLYMERASE E1 (NRPE1) are the largest subunits, respectively (Herr et al, 2005;Kanno et al, 2005;Onodera et al, 2005;Pontier et al, 2005). MORPHEUS' MOLECULE1 (MOM1) is also a plantspecific and still enigmatic protein that plays an important role in repressing transcription of intermediate heterochromatin (Habu et al, 2006). Notably, plants defective in MOM1 activity display no or only minor epigenetic changes at the released loci (Vaillant et al, 2006).…”
mentioning
confidence: 99%